Synthesis of Glibenclamide-Pregnenolone Conjugate and Its Relationship with Physico-chemical Descriptors log P, p, Rm, Vm, Pc and St - Figueroa-Valverde, Lauro; Diaz-Cedillo, Francisco; Lopez-Ramos, Maria; Garcia-Cervera, Elodia; Ancona-Leon, Josefina; E. Pool-Gomez, Jose (Asian Journal of Chemistry, 2011)
In this study, a glibenclamide-pregnenolone conjugate was synthesized. The route involved a reaction of substitution of chloride atom involved in the chemical structure of glibenclamide to form the compound 2 using sodium hydroxide. Additionally, the compound 2 was bound to pregnenolone succinate to form the glibenclamide-pregnenolone conjugate (4) in the presence of dicyclohexylcarbodiimide and p-toluene sulfonic acid. To delineate the structural chemical requirements of the compounds 2 and 4, some parameters such as the physico-chemical descriptors log P, p, Rm, Vm, Pc and St were calculated. The results showed an increase in log P, p, Rm, Vm, Pc values for 4 in comparison with compound 2. These data indicate that steric impediment, conformational preferences and internal rotation of compound 4 could influence the degree of lipophilicity of this compound.